Efficient, scalable syntheses of important intermediates in tribenzotriquinacene chemistry - Beaudoin, Daniel; Rominger, Frank; Mastalerz, Michael (Synthesis, 2015)
A new synthetic procedure for the synthesis of 1,4,7-tribromo-10-methyltribenzotriquinacene on multigram scale is reported. Its conversion into 1,4,7-trimethoxy-10-methyltribenzotriquinacene is also described. Both procedures are simpler and greener alternatives to the known ones, and the crystal structures of both compounds are disclosed.